The Phenomenon Of Artist Vlog Content On Millenials In Bengkulu City (Study Of Phenomenology On Millennials In Bengkulu City) - Eka Septi Rahmawati; Asnawati Asnawati; Sri Narti (Penerbit Jurnal Indonesia, 2021)
The purpose of this study is to find out the perspective of millennials in the city of Bengkulu on the phenomenon of artist vlog content. Data collection techniques that researchers use are interviews, documentation and observation. The data collection technique was purposive sampling by taking five informants from the millennial generation of Bengkulu city. After the data was obtained, it was analyzed using a descriptive qualitative study where the researcher conducted interviews with each informant for completeness of the data. This study uses the Merleau-Ponty perceptual phenomenology theory. The results of the research and discussion show that the millennial generation has the same perspective on the phenomenon of artist vlog content.